La prueba de microalbuminuria en la detección temprana de daño renal en pacientes diabéticos que acuden al hospital miguel león bermeo de chunchi durante el período mayo - octubre de 2013 - Barragán García, Brian Geovanny (2014)
Microalbuminuria is the earliest sign of nephroangiosclerosis and constitutes by itself, a risk factor for cardiovascular disease and chronic renal failure, which is the most feared complication and the end of the kidney damage in the decompensated arterial hypertension and of long evolution, where the microalbuminuria becomes a relevant value in its initial detection.